Extended Use of the Wearable Cardioverter-Defibrillator: Which Patients Are Most Likely to Benefit? - Boldizsar Kovacs; Sven Reek; Nazmi Krasniqi; Urs Eriksson; Firat Duru (Cardiology Research and Practice)
Background. Wearable cardioverter-defibrillators (WCD, LifeVest, ZOLL) can protect from sudden cardiac death bridging a vulnerable period until a decision on implantable cardioverter-defibrillator (ICD) implantation can be reached. WCD is commonly used for 3 months or less. It is unknown, which patients use WCD longer and which patients are most likely to benefit from it. Hypothesis. Extended use of WCD is reasonable in selected cases based on underlying heart disease and overall patient risk profile. Methods. We conducted a systematic and comprehensive research of all published clinical studies on PubMed reporting on the use of the WCD. Only original articles reporting on wear times and time to appropriate shocks were included in our analysis. Results. The search resulted in 127 publications. 14 parameters were reported necessary for inclusion in our analysis. Median wear times ranged from 16 to 394 days. The median wear time was especially long for patients suffering from nonischemic cardiomyopathy (NICM) (range: 50–71 days) and specifically peripartum cardiomyopathy (PPCM) (120 days) and for heart transplant candidates. There was a large variation of appropriate shocks according to indication for WCD use. In contrast to NICM in general, the number of appropriate shocks was particularly high in patients with PPCM (0 in 254 patients and 5 in 49 patients, respectively). The median and maximal time periods to the first appropriate shock were longest in patients with PPCM (median time to the first appropriate shock: 68 days). Conclusions. Prolonged use of WCD is not uncommon in available literature. Patients suffering from NICM and specifically PPCM seem most likely to have longer therapy duration with WCD with success. Careful patient selection for prolonged use may decrease the need for ICD implantation in the future; however, prospective data are needed to confirm this hypothesis.